Vector construction and transformation of 4CL1 gene into chinaberrytree (Melia azedarach L.) - Thanh, Ngo Van; Xiangning, Jiang; Huan, Ha Van; Hau, Nguyen Thi; Giang, Ho Van (VNU Journal of Science: Natural Sciences and Technology; Vol 26 No 3, 2010)
Abstract